Comprehensive Lichenometabolomic Exploration of Ramalina conduplicans Vain Using UPLC-Q-ToF-MS/MS: An Identification of Free Radical Scavenging and Anti-Hyperglycemic Constituents - Tatapudi Kiran Kumar; Bandi Siva; Ajay Anand; Komati Anusha; Satish Mohabe; Araveeti Madhusudana Reddy; Françoise Le Devehat; Ashok Kumar Tiwari; Joël Boustie; Katragadda Suresh Babu (Molecules, 2022)
In this study, we propose ultra-performance liquid chromatography coupled with quadrupole/time-of-flight mass spectrometry (UPLC-QToF-MS/MS)-guided metabolite isolation as a choice analytical approach to the ongoing structure–activity investigations of chemical isolates from the edible lichen, Ramalina conduplicans Vain. This strategy led to the isolation and identification of a new depside (5) along with 13 known compounds (1–4, 6–14), most of which being newly described in this lichen species. The structures of the isolates were established by detailed analysis of their spectral data (IR, NMR, and Mass). The acetone extract was further analyzed by UPLC-Q-ToF-MS/MS in a negative ionization mode, which facilitated the identification and confirmation of 18 compounds based on their fragmentation patterns. The antioxidant capacities of the lichen acetone extract (AE) and isolates were measured by tracking DPPH and ABTS free radical scavenging activities. Most isolates displayed marked radical scavenging activities against ABTS while moderate activities were observed against DPPH radical scavenging. Except for atranol (14), oxidative DNA damage was limited by all the tested compounds, with a marked protection for the novel isolated compound (5), as previously noted for the acetone extract (p < 0.001). Furthermore, compound (4) and acetone extract (AE) have inhibited intestinal α-glucosidase enzyme significantly (p < 0.01). Although some phytochemical studies were already performed on this lichen, this study provided new insights into the isolation and identification of bioactive compounds, illustrating interest in future novel analytical techniques.